Definitions of Transnational Higher Education - Wilkins, Stephen (International Higher Education, 2018)
Transnational higher education involves providers and programs crossing national borders. The providers take a variety of forms, with different ownership structures, objectives, strategies, disciplines, and types of student. The purpose of this article is to identify the different types of transnational education providers, so that these institutions can be categorized and defined. The focus is only on institution mobility, and therefore program mobility—such as distance education, franchised programs, and joint or dual degrees—are outside the scope of the article.